2016
DOI: 10.1038/srep28628
|View full text |Cite
|
Sign up to set email alerts
|

Induction of a stable sigma factor SigR by translation-inhibiting antibiotics confers resistance to antibiotics

Abstract: Antibiotic-producing streptomycetes are rich sources of resistance mechanisms against endogenous and exogenous antibiotics. An ECF sigma factor σR (SigR) is known to govern the thiol-oxidative stress response in Streptomyces coelicolor. Amplification of this response is achieved by producing an unstable isoform of σR called σR′. In this work, we present evidence that antibiotics induce the SigR regulon via a redox-independent pathway, leading to antibiotic resistance. The translation-inhibiting antibiotics enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(43 citation statements)
references
References 52 publications
2
41
0
Order By: Relevance
“…One other S. coelicolor ECF sigma factor, σ R , has been tied to antibiotic resistance [96]. In the presence of translation-inhibiting antibiotics such as chloramphenicol and erythromycin, expression of a stable isoform of σ R increases [96].…”
Section: Ecf Sigma Factor-mediated Systems In Gram-positive Bacteriamentioning
confidence: 99%
See 2 more Smart Citations
“…One other S. coelicolor ECF sigma factor, σ R , has been tied to antibiotic resistance [96]. In the presence of translation-inhibiting antibiotics such as chloramphenicol and erythromycin, expression of a stable isoform of σ R increases [96].…”
Section: Ecf Sigma Factor-mediated Systems In Gram-positive Bacteriamentioning
confidence: 99%
“…In the presence of translation-inhibiting antibiotics such as chloramphenicol and erythromycin, expression of a stable isoform of σ R increases [96]. A sigR mutant is more sensitive than the parent strain to the antibiotics that induce σ R expression, but is not more sensitive to unrelated antibiotics, such as ampicillin [96].…”
Section: Ecf Sigma Factor-mediated Systems In Gram-positive Bacteriamentioning
confidence: 99%
See 1 more Smart Citation
“…Based on phenotypic analysis, WhiD is required for the late stages of sporulation, whereas, disruption of wblC lead to mutants that were hypersensitive to antibiotics, as observed for M. tuberculosis whiB7 mutants [185,186]. Recent work by Yoo et al [187] showed that WblC (WhiB7) induces a stable isoform of the ECF sigma (σ) factor R that governs thiol-oxidative stress, and, that WblC binding to the sigRp1 promoter responds to antibiotic treatment in vivo. A similar phenomenon appears to exist in M. tuberculosis, suggesting an important role for WblC/WhiB7 in innate antibiotic resistance [187].…”
Section: Wbl Proteins In Streptomyces Coelicolormentioning
confidence: 99%
“…Recent work by Yoo et al [187] showed that WblC (WhiB7) induces a stable isoform of the ECF sigma (σ) factor R that governs thiol-oxidative stress, and, that WblC binding to the sigRp1 promoter responds to antibiotic treatment in vivo. A similar phenomenon appears to exist in M. tuberculosis, suggesting an important role for WblC/WhiB7 in innate antibiotic resistance [187].…”
Section: Wbl Proteins In Streptomyces Coelicolormentioning
confidence: 99%